The impact of Syrian refugees on patient demographics and type 2 diabetes across five public health centers in Lebanon. (2021) - Makhoul, Peter; Tcheroyan, Raya; Ammar, Walid; Hamadeh, Randa; Zalloua, Pierre; Nabbout, Ghassan
No abstract available